Extensions of Nice Bases on ULM Subgroups of Primary Abelian Groups With Totally Projective Quotients - Danchev, Peter; Keef, Patrick (Sarajevo Journal of Mathematics, 2024)
Suppose G is an abelian p-group, α is an ordinal and G/p^αG is totally projective. We show that G has a nice basis if and only if G/p^αG has a nice basis. This extends results of Danchev in Bull. Malaysian Math. Sci. Soc. (2010), Bull. Allah. Math. Soc. (2011) and An. St. Univ. Ovidius Constanta (2012), as well as joint work with Keef in Rocky Mount. J. Math. (2011). 2010 Mathematics Subject Classification. 20K10.